Variation of boron concentrations in the wood and bark of some tree - Nazli AK TUTUNCU; Halil Baris OZEL; Hakan SEVIK; Ramazan ERDEM (GSC Online Press, 2024)
Air pollution has become one of the most critical threats to human health in the last century. Heavy metals are among the components of air pollution that threaten human health the most. Boron is one of the heavy metals whose use has been increasing in recent years due to its use in more than 250 fields in industry. Due to intensive use, boron concentrations in receiving environments are constantly increasing. However, boron, one of the important heavy metals, can cause significant health problems when inhaled from the air and taken into the human body. Therefore, monitoring the changes in boron concentration in the air is very important. In this study, species, organ, and directional changes of boron concentration in Tilia tomentosa, Robinia pseudoacacia, Cedrus atlantica, Pseudotsuga menziesii, and Fraxinus excelsior species growing in Düzce, one of the five most polluted cities in Europe. The study results show that boron concentrations are generally higher in the outer bark. Regarding species, the lowest values were obtained in P. menziesii, and the highest were obtained in R. pseudoacacia. The highest B concentrations in wood were obtained in R. pseudoacacia, and it is thought that this species can be used effectively to reduce B pollution.
Keywords: Accumulator; Heavy metal; Wood; Boron